Features of the course of acute respiratory infections in rheumatological patients during the military aggression by the Russia's military aggression against Ukraine. - Grishyna, Olena; Menkus, Olena (Annals of Mechnikov's Institute, 2023)
Introduction. On February 24, 2022, a large-scale military aggression by the Russian Federation against Ukraine began. As a result, Kharkiv was on the front line, regularly subjected to artillery and rocket attacks. Kharkiv is one of the largest metropolises in Eastern Europe with a population of one and a half million people. Many residents were forced to leave the city, becoming internally displaced persons (IDPs) or refugees. Our patients are not an exception. The aim of our study was to investigate the course of acute respiratory infections (ARIs) in rheumatological patients in the frontline city of Kharkiv, comparing them with patients who relocated to relatively safe areas. Material & methods. In July-August 2022, we conducted a patient survey that separately assessed ARIs since 24 February 2022 and their course depending on the patients' location. In general, it was a retrospective study using a voice/video questionnaire. In January and April 2023, patients were interviewed about the incidence of ARIs for the period from September 2022 to April 2023. Results & Discussion. We contacted 143 patients. Among them, 66 (46.2%) patients stayed in Kharkiv and 77 (53.8%) left: 51 (66.2%) moved to other regions of Ukraine (became IDPs), and 26 (33.8%) moved abroad. Between February and June 2022, some of our patients had ARIs. To analyze the course of ARIs, we chose patients with psoriatic arthritis and ankylosing spondylitis, as these groups differed only in gender (using Fisher's extract test, p = 0.214, which allows us to say that there is no influence of gender on the frequency of infections in these groups). In group 3 (n=53 - patients who did not migrate), 6 people (11.3%) had ARIs, and in group 4 (n=27 - IDPs) - 13 (48.1%), p=0.0003. The course of the disease was also more severe in group 4 due to the duration of symptoms (M ± SD, days) 10.9 ± 3.1 vs. 28.3 ± 8.4, p = 0.0001 and the number of symptoms per patient (M ± SD) 3.4 ± 1.1 vs. 5.3 ± 1.5, p = 0.013. A year later, when the same patients were interviewed (group 3 increased due to returning patients and is further labeled as group 3a, n=61, and group 4 decreased accordingly and is further labeled as group 4a, n=19). From September 2022 to April 2023, 23 patients in group 3a (3.1%) and 6 (31.6%) in group 4a (p = 0.9) suffered from respiratory infections. There were no differences in the course and severity of the diseases between the groups. Thus, patients in the IDPs group were more prone to developing infections in the first months of the war. This may be due to living in crowded places (e.g., gyms), canteens for IDPs, places of humanitarian aid distribution, etc. Patients who rented separate apartments also reported significant crowding of people in public places, transportation, and even on the streets. Two patients changed their place of residence 2 times and 1 to 4 times. Overall, the number of contacts per patient in group 2 was incomparably higher than in group 3. A longer course of disease was noted in IDPs. The leading symptom was cough, which lasted longer than all symptoms (we didn't take into account such a symptom as faintness, since the patients themselves didn't emphasize it). In general, this group has a more severe course of the disease, which is evidenced by a significantly higher number of symptoms per 1 patient. In Kharkiv, there were patients who lived in areas that were less often subjected to artillery shelling. The second characteristic feature of patients remaining in the city is the presence of work that cannot be done remotely. Also, these patients did not spend a long time in basements or bomb shelters. By the second year of the war, the situation with respiratory viral infections had leveled out between the residents of Kharkiv and the patients who had gone to safer areas. This applies to both the frequency of illness and the severity of the course. All patients in group 4a already rented separate housing; someone in the family (if not all family members) was working. Few turned to humanitarian aid; most lived in small towns and used public transport infrequently. The Kharkov region was deoccupied almost completely in September 2022. Patients in group 3a, on the contrary, became more active; the number of contacts significantly increased. They actively used public transport, especially considering that the municipality still covered the fare; many patients returned to their workplaces. Thus, household and socio-economic differences between the groups were leveled out, which likely had an impact on the course of illnesses, including acute respiratory infections (ARIs). The effectiveness of quarantine for infectious diseases has been demonstrated since the Middle Ages. We did not anticipate that in the 21st century it would be possible to supplement the data with such an example. Conclusion. The first year of military actions was accompanied by an increase in the incidence of ARIs and their more severe course in the group of patients with PsA and AS who became IDPs compared to the same patients who remained in Kharkiv and were in relatively satisfactory household conditions. In the second year of military aggression, these groups became comparable both in terms of frequency and severity of ARIs. Key words: rheumatic diseases, acute respiratory infections, military aggression, migration.